Wild Radish--Biology and Control - Jason A. Ferrell; Greg E. MacDonald (EDIS)
Wild radish is one of the most common and problematic pasture weeds in the Florida Panhandle. It is found throughout the state and can be a serious pest in other crops including peanut, corn and winter vegetables. This publication provides information concerning the biology and growth of wild radish, the problems associated with its presence in wheat and other small grains and methods of control and management. This document is SS-AGR-236, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published September 2005.